Genetic algorithm optimization of a wideband rectangular patch antenna with an asymmetric u-slot and partial ground for Ku-band satellite communication - Al Gburi, Ahmed Jamal Abdullah; Bennioui, Fatim-Zahra; Khabba, Asma; Bouslam, Karima Ait; Wakrim, Layla; Ibnyaich, Saida; Zeroual, Abdelouhab; Zakaria, Zahriladha (Electromagnetics Academy, 2025)
This paper presents an innovative microstrip patch antenna (MPA) designed and optimized for Ku-band satellite communications. The proposed design incorporates an asymmetric U-shaped slot and a partial ground plane, constructed using an FR4 substrate with dimensions of 18 × 16 × 1.6 mm3 (0.416λ × 0.37λ × 0.03λ, where λ is the wavelength at 6.94 GHz). A genetic algorithm is employed to optimize the U-shaped slot and ground plane dimensions, enhancing the antenna’s wideband performance while preserving its compact form factor. Simulation results indicate that the optimized design achieves two operational frequency bands with reflection coefficients (S11) less than −10 dB: a narrowband from 6.83 GHz to 7 GHz, with a resonant frequency of 6.94 GHz, and a wideband from 10.26 GHz to 17.19 GHz, with a resonant frequency of 14.94 GHz. This extensive frequency range enables the antenna to effectively support direct broadcast services (DBSs) and fixed satellite services (FSS). The design’s effectiveness was confirmed through prototype fabrication and testing, demonstrating strong agreement with simulated results and proving the antenna’s compactness and exceptional wideband performance.